Knowledge and beliefs about vaccination in pregnant women before and during the COVID-19 pandemic - Bruno, Stefania; Nachira, Lorenza; Villani, Leonardo; Beccia, Viria; Di Pilla, Andrea; Pascucci, Domenico; Quaranta, Gianluigi; Carducci, Brigida; Spadea, Antonietta; Damiani, Gianfranco; Lanzone, Antonio; Federico, Bruno; et al. (Frontiers in Public Health, 2022)
Vaccine hesitancy threatens the health of populations and produces challenges for Public Health professionals. Strategies to reduce it aim at improving people’s risk perception about vaccine-preventable diseases, filling knowledge gaps about vaccines and increasing trust in healthcare providers. During pregnancy, educational interventions can provide knowledge about safety and efficacy of maternal and childhood vaccinations. Fighting hesitancy and clarifying doubts is fundamental during the COVID-19 pandemic, which may have affected people’s knowledge and beliefs towards vaccination. This study aimed at assessing if the advent of the pandemic was associated with changes in pregnant women’s knowledge and beliefs towards vaccination, and their trust in healthcare services. A repeated cross-sectional study was conducted through self-reported questionnaires in a teaching hospital in Rome, Italy, where educational classes about vaccinations are routinely held as part of a birthing preparation courses. Data were collected on a sample of pregnant women before and during the pandemic. Free-of-charge flu vaccinations were offered to all course participants and their partners, and their adherence was assessed. The proportion of pregnant women stating that vaccines have mild side effects and are sufficiently tested increased from 78.6% to 92.0% (p= 0.001) and from 79.4% to 93.2% (p= 0.001), respectively. There was a reduction from 33.0% to 23.3% (p= 0.065) in the proportion of those declaring that healthcare workers (HCWs) only gave information on the benefits and not on the risks of vaccines, and a reduction from 27.3% to 12.1% (p= 0.001) in those reporting that vaccines are an imposition and not a matter of free choice for mothers. Trust in National Health Service (NHS) operators slightly decreased. Among participants, the monthly flu vaccination adherence ranged from 50.0% in November to 29.2% January for 2019-20 flu season, and from 56.3% in September to 14.5% in January for 2020-21, showing a higher vaccination acceptance in the earlier months of the 2020-21 flu season. The pandemic may have positively affected pregnant women's knowledge and opinions about vaccinations and trust in HCWs, despite a possible negative impact on their perceptions about NHS operators. This should inspire Public Health professionals to rethink their role as health communicators.